Health, fitness, physical activity, and morbidity of middle aged male factory workers. I. Issue 11 (November 1986) - Tuxworth, W; Nevill, A M; White, C; Jenkins, C
Abstract : A description of the fitness, physical activity of lifestyle, and some aspects of health status and attitudes in a population of male factory workers aged 35-60 is presented as the first part of a report on a study of morbidity in this population. A total of 1394 subjects were included, undergoing medical examination, fitness testing by bicycle ergometry, assessment of body fat, and interview questionnaire. The inter-relation of fitness, body composition, habitual exertion, health risk factors, and attitudes to exercise are discussed. Fitness levels are compared with those reported in other studies and discussed in terms of capacity for walking and running and in relation to criteria for health benefit. In these two latter respects fitness appears to be inadequate among the great majority of those tested, although it is comparable with that reported by several other recent studies. Fitness is associated with physical activity of leisure but not that of work. Only relatively strenuous physical activity in leisure time appears to be related to fitness, and is only participated in by some 28% of the sample. Cycling has the strongest association with fitness of all the physical activity variables. Blood pressure and percentage body fat are also associated, inversely, with fitness, the latter not unexpectedly because of the weight related measure of fitness.